2020
DOI: 10.1515/zna-2020-0098
|View full text |Cite
|
Sign up to set email alerts
|

Structural and wavelength dependent optical study of thermally evaporated Cu2Se thin films

Abstract: The present work encloses structural and optical characterization of copper (I) selenide (Cu2Se) thin films. The films having thickness 85 nm have been deposited using thermal evaporation technique in initial step of work. The structural and morphological studies of deposited thin films are then done by X-ray diffraction (XRD), scanning electron microscope (SEM), and surface profilometer measurements. Later on, ultraviolet-visible-near-infrared (UV-VIS-NIR) spectrophotometer and Raman spectroscopic measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…However, the nanoparticle sizes vary between 100 and 200 nm. Similar uniform nanoparticle deposition over the film surface was observed for Fe 2 O 3 [20], Cu 2 Se [21] and TiO 2 thin films [22]. The nanoparticle size distribution in the films can be improved by annealing them at high temperatures for longer periods.…”
Section: Methodssupporting
confidence: 62%
“…However, the nanoparticle sizes vary between 100 and 200 nm. Similar uniform nanoparticle deposition over the film surface was observed for Fe 2 O 3 [20], Cu 2 Se [21] and TiO 2 thin films [22]. The nanoparticle size distribution in the films can be improved by annealing them at high temperatures for longer periods.…”
Section: Methodssupporting
confidence: 62%
“…The variation in reflectance was primarily attributed to the effects of material properties and surface topography, whereas the change in the reflectance of the films was primarily attributed to the refractive index of the materials and the roughness of the surface. Hirate et al and Yadav et al revealed that below 1200 nm, the trends of the change in the refractive index of CZTSe, Cu x Se, and CTSe are virtually the same [39,40]. Thus, little change occurred in the reflectance characteristics of the four samples.…”
Section: Resultsmentioning
confidence: 95%
“…The PCE of the Cu 2 Se/Si solar cell presented here surpasses these reported values for the solar cells based on CuO/Si or Cu 2 O/Si systems. Yadav et al [56] reported that the refractive index n and the extinction coefficient K for Cu 2 Se in the visible light region (390-780 nm) range from 4.62 to 2.63 and from 0.569 to 0.613, respectively. Consequently, the reflectance R = [(n−1) 2 + K 2 ]/[(n + 1) 2 + K 2 ] for the Cu 2 Se film lies between 42% and 22%.…”
Section: Resultsmentioning
confidence: 99%